PENGARUH TATA KELOLA PERUSAHAAN TERHADAP TINGKAT PENGUNGKAPAN INTERNET FINANCIAL REPORTING PADA PERUSAHAAN MANUFAKTUR TAHUN 2022 - MH. Yuve Putra Haryadi; Mutiara Tresna Parasetya (Diponegoro Journal of Accounting, 2025)
This study aims to examine the effect of corporate governance on Internet Financial Reporting (IFR) in manufacturing companies listed on the Indonesia Stock Exchange (IDX). Corporate governance is characterized by managerial ownership, institutional ownership, firm size, and audit committee.The population in this study are manufacturing companies included in the Indonesia Stock Exchange in 2022. The sampling method used in this research is purposive sampling. The total sample in this study was 86 research samples. The data obtained in this study were obtained from the Indonesia Stock Exchange and the company's website. Hypothesis testing in this study uses multiple linear regression analysis with the help of SPSS 26.0 software.The results of this study indicate that managerial ownership and audit committee have a positive effect on Internet Financial Reporting. On the other hand, institutional ownership and Company Size have a negative effect on Internet Financial Reporting.